2011
DOI: 10.1021/nn200313t
|View full text |Cite
|
Sign up to set email alerts
|

Nano-engineered Flavin-Dependent Glucose Dehydrogenase/Gold Nanoparticle-Modified Electrodes for Glucose Sensing and Biofuel Cell Applications

Abstract: A three-dimensional composite consisting of the oxygen-insensitive flavin-dependent glucose dehydrogenase, GDH, and Au nanoparticles (NPs) is assembled on a Au surface using an electropolymerization process. The bis-aniline-cross-linked GDH/Au NPs composite reveals effective electrical contact with the electrode (ket=1100 s(-1)), and the effective bioelectrocatalyzed oxidation is driven by the enzyme/NPs matrix. The GDH/Au NPs-functionalized electrode is implemented as an amperometric glucose sensor, and it re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(120 citation statements)
references
References 34 publications
1
117
1
1
Order By: Relevance
“…S6). These bioelectrocatalytic functions of the BOD/CNTs were previously implemented to develop biofuel cells using glucose 49,50 or ethanol 49 as fuels. Accordingly, the pMBQ/ PSII photoanode was coupled to the BOD/CNTs cathode ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S6). These bioelectrocatalytic functions of the BOD/CNTs were previously implemented to develop biofuel cells using glucose 49,50 or ethanol 49 as fuels. Accordingly, the pMBQ/ PSII photoanode was coupled to the BOD/CNTs cathode ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, polymer brushes based on a photo-responsive polymers have received much interest as colorimetric sensors due to their ability to report colorimetrically the presence or absence of the ion-ligand complex (76). A photochemically and electrochemically triggered gold nanoparticle sponge has been prepared in Willner's group by attaching spiropyran and thioaniline moieties to the particles (77,78). Interestingly, it was reported that this composite can be used as an Figure 1 The operational principles of a device consisting of a sensor and an Al/air battery separated by a wax barrier.…”
Section: Opportunities For Materials Science In Biomedical Sensingmentioning
confidence: 99%
“…Recent development has focused on improving the immobilization and stability of the enzymes [57,58]. Enzymes immobilized to nanosized scaffolds such as spheres, fibres and tubes have all recently been reported [59][60][61]. The premise of using nanoscale structures for immobilization is to reduce diffusion limitations and maximize the functional surface area to increase enzyme loading.…”
Section: Biosensorsmentioning
confidence: 99%